2017
DOI: 10.1364/ol.42.005282
|View full text |Cite
|
Sign up to set email alerts
|

Off-axis tilt compensation in common-path digital holographic microscopy based on hologram rotation

Abstract: We present a simple and effective compensation method for the off-axis tilt in common-path digital holographic microscopy (CPDHM) by introducing a rotating operation on the hologram. The proposed method mainly requires a digital reference hologram (DRH), which is a rotated version of the original one; it is assumed to be easy to obtain by rotating the specimen's hologram 180°. In this way, the off-axis tilt could be removed by subtracting the retrieved phase of DRH from the retrieved phase of the original holo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…μ is radius of curvature. According to our previous works [9], [24], it is clearly shown that after doing geometrical transformations for unwrapped phase (+1 order) of original hologram, the specimen's phase is also performed by same transformation operations. Thus, the transformation phase is phase compensation mask used to compensate phase aberrations in DHM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…μ is radius of curvature. According to our previous works [9], [24], it is clearly shown that after doing geometrical transformations for unwrapped phase (+1 order) of original hologram, the specimen's phase is also performed by same transformation operations. Thus, the transformation phase is phase compensation mask used to compensate phase aberrations in DHM.…”
Section: Methodsmentioning
confidence: 99%
“…One common problem of these methods [6]- [8] is that they usually require many conditions such as the previous parameters of setup, a two-shot operation, or additional computational fitting procedures. Recently, a rotation-based method [9] is reported to effectively remove off-axis tilt without these requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 Besides, a hologram rotation-based method is proposed, in particular, for getting rid of the off-axis tilt as well as the parabolic phase aberration. 25,26 Despite the success and flexibility of current numerical approaches, manual operations of selecting a flat region as reference surfaces 17,19 are required, an assumption is made that the object is so thin that it is just a small perturbation in the aberration contribution to the overall reconstructed phase distribution, 18,21 or only low-order aberrations such as the phase curvature introduced by the MO can be removed. 18 It is worth noting that the polynomial-based method is a semiautomatic method since it requires background information to find the phase residual, which is detected by manually cropping a flat background area as Refs.…”
Section: Introductionmentioning
confidence: 99%
“…22,27 Furthermore, manual filtering and centering 23 or hypothesis of a thin phase object 24 is inevitable in the spectrum-based analysis, and the self-hologram rotation is solely suitable for tilt aberration compensation. 25 Recently, a learning-based method is proposed to automatically detect the specimen-free background for the subsequent fitting using Zernike polynomials. 28 Aberration removal is further encapsulated in holographic reconstruction and thus can be automatically compensated during the feed-forward propagation along the network.…”
Section: Introductionmentioning
confidence: 99%